Flowability Properties of Commercial Distillers Dried Grains with Solubles (DDGS) - Rosentrater, Kurt A.; Muthukumarappan, K.; Bhadra, Rumela (My University, 2009)
Distillers dried grains with solubles (DDGS), the major coproduct from the corn-based fuel ethanol industry, is primarily used as livestock feed. Due to high protein, fiber, and energy contents, there is a high demand for DDGS. Flowability of DDGS is often hindered due the phenomenon of caking. Shipping and handling of DDGS has thus become a major issue due to bridge formation between the DDGS particles. The objective of this investigation was to measure flowability characteristics of DDGS samples from five ethanol plants in the north central region of the United States. Carr and Jenike tests were performed and the resulting data were mathematically compared with a previously developed empirical model. The largest particles had an average geometric mean diameter (GMD) of 1.19 mm, while the lowest particle size had an average GMD of 0.5 mm. Soluble solid levels were ≈10.5–14.8% (db). The effective angle of friction (δ) was 43.00–57.00°. Additionally, a few parameters exhibited fairly high linear correlations, including aerated and packed bulk densities (r = 0.97), geometric standard deviation and Carr compressibility (r = 0.71), geometric standard deviation and Hausner ratio (r = –0.70). Overall flowability assessment indicated that the commercial DDGS samples did have the potential for flow problems, although no samples exhibited complete bridging. Quantifying DDGS flowability is a necessary step toward overcoming this logistical challenge facing the fuel ethanol industry.
Keywords: Flowability properties; Commerical DDGS; Distillers dried grains with solubles (DDGS); Corn-based fuel ethanol